(untitled) (Docentes 2.0 Journal, 2020)
The World Health Organization (WHO) has declared COVID-19 a pandemic due to its speed of spread, the education sector is not immune to it. Schools, with digital platforms, have the option of making pedagogical processes more flexible in students from the articulation of web applications to continue with the educational service. The present study aimed to analyze the integration of ICT tools as a didactic strategy in collaborative learning in academic training spaces as part of the rethinking of teaching. For the research work, the mixed approach was used. The instrument used was the questionnaire, which allowed diagnosing the management and use of ICT tools to be able to respond to the individual and collective needs raised by educators and the directors of educational institutions. In the results obtained, it was evidenced that the educator had to assume a new role mediated by ICTs in the face of mandatory preventive isolation. Another finding was the strengthening of the use of ICT in the virtual context of the classes generated by the educators, given a new impetus to the training process based on innovative significant experiences. It is concluded that the pandemic generated a disruption in the educational system, for this reason, the directives of educational institutions should have as effective learning alternatives the virtual education model as an added value to their educational proposal in response to the new post-COVID context -19.